Public policies for wellbeing with justice : a theoretical discussion based on capabilities and opportunities - Krishnakumar, Jaya (Pontificia Universidad Católica del Perú. Fondo Editorial, 2017)
In this paper, we defend the idea that combining these theories sheds new and useful light to understand wellbeing and its relation to public policies, because of the way they complement positive and normative reasoning, giving answers to both our questions. Throughout this document, we make the case that neither CA nor EOp, on its own, presents a combination of wellbeing and justice that can provide formal policy guidelines for improving well-being with justice through an appropriate optimality principle. We present arguments in search of clear answers to both our questions and show that an ordered integration of elements from both approaches leads to a plausible solution. The paper is structured as follows: in section 2 we present some basic statements of Sen’s and Roemer’s theories, briefly recalling their essentials. In sections 3 and 4 we analyze plausible responses to the two questions raised in these introductory paragraphs, respectively, around the CA and the EOp approach. In section 5 we propose a theoretical combination as well as a technical derivation of our optimal policy and illustrate its usefulness. Finally section 6 concludes
Páginas 99-125
Keywords: Política pública; Justicia social; https://purl.org/pe-repo/ocde/ford#5.00.00